Construction of amorphous interface in an interwoven NiS/NiS2 structure for enhanced overall water splitting. Issue 18 (25th April 2018) - Li, Qun; Wang, Dewen; Han, Ce; Ma, Xiao; Lu, Qingqing; Xing, Zhicai; Yang, Xiurong
Abstract : Here, we describe the synthesis of a novel interwoven NiS/NiS2 structure with an amorphous interface accomplished by carrying out a one-step thermal decomposition of nickel sulfate and thiourea. Abstract : Here, we describe the synthesis of a novel interwoven NiS/NiS2 structure with an amorphous interface accomplished by carrying out a one-step thermal decomposition of nickel sulfate and thiourea. A partial phase transition from NiS2 to NiS induced the amorphous interface in NiS/NiS2 and was expected to separate the H* and H − intermediates onto different interface sites, and to reduce the interfacial energy and charge-transfer resistance as well. When NiS/NiS2 was applied as an electrocatalyst for overall water splitting (OWS), it achieved a geometrical current density of 100 mA cm −2 at a low overpotential of 248 mV for the hydrogen evolution reaction (HER) and 416 mV for the oxygen evolution reaction (OER), obviously superior to those of the single-phase catalysts. In addition, it was also employed as an efficient bifunctional catalyst for OWS, yielding a current density of 10 mA cm −2 at a voltage of 1.62 V.